Three Decades of River Bank Erosion and Accretion Appraisal Along Bank Line Shifting Trend in A Transboundary River, Teesta Floodplain of Bangladesh - Parvej, Masud; Masum, Kazi Mohammad; Fahim, Md. Sahinur Islam; Redowan, Mohammad (Geoplanning: Journal of Geomatics and Planning, 2024)
As the world's largest delta, Bangladesh possesses distinctive geomorphology dominated by transboundary rivers, making it vulnerable to climatic hazards such as river erosion that causes severe loss of land and other resources. Using four Landsat imageries of 1991, 2001, 2011 and 2021 the current study analyzed the amount and trend of river erosion and accretion on the Teesta Floodplain of Bangladesh for three decades. Findings indicate that the Teesta River experiences severe bank erosion and accretion regularly, causing bank line shifting and thus significant affecting the land-use/land-cover (LULC) change of the area. Between 1991 and 2021, approximately 194 square kilometers of land were eroded, while an equivalent area of land was accreted. Approximately 1072 km2 of agricultural land was converted into other categories, with the settlement area gradually increasing. This trend of changes shows that agricultural land and water-bodies will reduce in the next two decades while barren land and settlement areas will increase. The agricultural lands and barren lands have a greater chance of being occupied by settlement areas. At the same time, crop production patterns will move to those crops that require less water due to the reduction of water-bodies. Reduced flow during the dry season and massive discharge during the monsoon from India's Gajoldoba barrage caused massive siltation and erosion. Comprehensive river management and restoration with an intergovernmental treaty or understanding between India and Bangladesh is required to resolve this crisis in the long run.